The antibiofilm potential and therapeutic adjuvant properties of Salvia aurea and Sphedamnocarpus pruriens, against Mycobacterium smegmatis - Lall, Namrita (University of Pretoria, 2023)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2023.